FACTORS FOR THE OCCURRENCE OF ROAD TRAFFIC INJURIES AND BETTER CARE OF INJURED PERSONS - Peličić, Damir; Ristić, Branko; Radević, Svetlana (HEALTH CARE, 2024)
This paper will present information from relevant data sources on road traffic injuries, risk factors, and the importance of emergency care of the injured. According to the estimates from the World Health Organization (WHO), approximately 1.19 million people die in road traffic accidents each year, while the number of deaths due to road traffic accidents is 15 per 100,000 inhabitants. It is the leading cause of death for children aged 5 to 29 years and the 12th leading cause of death when all ages are observed.  Efficient trauma care is a priority in all health care systems. Given the high mortality and incidence of trauma, it is necessary to consider all potential risk factors that affect the outcome of treating the injured. Factors such as the availability of adequate healthcare, emergency medical service response time, trauma team experience and organization, distance to hospital facilities, and their equipment and expertise for adequate care of severely injured patients directly influence the quality and outcome of patient care and increase the chances of survival. This paper provides a thorough examination of the issues surrounding road traffic accidents and highlights key aspects that affect the quality of healthcare of the injured, while also emphasizing the importance of an appropriate response and organization of healthcare systems to improve treatment outcomes and reduce the mortality rate in traffic accidents.
Keywords: traffic trauma, risk factors, trauma registry, prevention